2008
DOI: 10.1208/s12249-008-9159-0
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release Hydrophilic Matrix Tablet Formulations of Isoniazid: Design and In Vitro Studies

Abstract: Abstract. The aim of the present investigation was to develop oral controlled release matrix tablet formulations of isoniazid using hydroxypropyl methylcellulose (HPMC) as a hydrophilic release retardant polymer and to study the influence of various formulation factors like proportion of the polymer, polymer viscosity grade, compression force, and release media on the in vitro release characteristics of the drug. The formulations were developed using wet granulation technology. The in vitro release studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 27 publications
5
30
0
Order By: Relevance
“…In order to establish the experimental setup, it was necessary to determine the solubility of INH and RFB in the specific medium. The solubility of INH in PBS pH 7.4 is reported in the literature as 274˘4.79 mg/mL [57]. In the absence of a value reported in the literature, an experimental determination has defined the maximum solubility of RFB in PBS pH 7.4 + 1% Tween 80 ® as 0.496 mg/mL.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…In order to establish the experimental setup, it was necessary to determine the solubility of INH and RFB in the specific medium. The solubility of INH in PBS pH 7.4 is reported in the literature as 274˘4.79 mg/mL [57]. In the absence of a value reported in the literature, an experimental determination has defined the maximum solubility of RFB in PBS pH 7.4 + 1% Tween 80 ® as 0.496 mg/mL.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…The influence of HPMC K100 LV CR, however, was found to be less prominent as compared to the PEO 303 on the bioadhesion strength. However, the bioadhesion characteristics of HPMC K100 LV CR can be attributed owing to its swellable nature by polymer relaxation mechanism, which helps in attachment of the dosage form with the gastric mucosa with the help of entanglement of the polymer chains with mucin chains (33). Overall, the studies revealed maximum bioadhesion strength of the prepared formulation at higher levels of PEO 303 and intermediate levels of HPMC K100 LV CR, where both interact synergistically for exhibiting the optimal bioadhesion.…”
Section: Characterization Of the Floating-bioadhesive Tabletsmentioning
confidence: 92%
“…Thus, higher amounts of HPMC and lower amounts of sodium CMC favor the drug release. The amounts of X 1 and X 2 show negative effect on Q 6 . Hence, it can be concluded that both factors show release retardant effect at 6 h. The amounts of X 1 and X 2 show positive effect on SI.…”
Section: Full Factorial Designmentioning
confidence: 94%
“…The drug release pattern is a complex phenomenon at the molecular level, it involves water penetration, polymer swelling as well as drug dissolution, diffusion and polymer erosion process. [3][4][5][6] For drugs with a narrow absorption window in the GI tract, the challenging task was not only to prolong drug release but the retention of the dosage form in the upper GI tract. This results in increase bioavailability, reduced dose, and frequency for drug administration.…”
Section: Introductionmentioning
confidence: 99%